Review of space habitat designs for long term space explorations. (1st April 2021) - Chen, Muhao; Goyal, Raman; Majji, Manoranjan; Skelton, Robert E.
Abstract: This review paper attempts to provide a useful reference for space habitat designs that advance the ability of humans to live in space for long periods of time. Five space habitat design concepts are reviewed with the principal aim of addressing the five fundamental problems in long term space exploration: artificial gravity, efficient radiation protection, sustainable food, growth strategy, and commercial values. The design of principal categories of life support systems, habitat subsystems, economics and cost reduction approaches are presented with a focus on establishing useful sources of fundamental issues in the literature, as well as highlighting important research directions and topics. Humans have enjoyed isolated successes in space, but the international space station (ISS) is going to retire soon. The space habitat design for long-duration use will be the next ambitious space program with contributions from the world-wide scientific and technical community. The overarching theme of the paper is to show the diversity, richness, and fundamental problems of habitat designs that have been undertaken in the last 60 years of space exploration.